Use and conservation status of medicinal plants in the Cape Peninsula, Western Cape Province of South Africa - Mintsa Mi Nzue, Agnan Pierre (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScConsEcol(Conservation Ecology and Entomology)--University of Stellenbosch, 2009.